High-throughput Cell Encapsulation in Monodisperse Agarose Microcapsules Using a Microfluidic Device - Monette-Catafard, Nicolas (Université d'Ottawa / University of Ottawa, 2014)
Over the last decade, microfluidics has emerged as a distinct new field with promising applications for diverse research areas. The ability to precisely control fluids at the microscale allows the execution of a variety of programmable semi-automatic operations on the same device, effectively forming a lab-on-a-chip. In particular, droplet-based microfluidic systems – which reliably generate highly uniform microdroplets at a high throughput – enable the controlled compartmentalization of biological material and have the potential to influence mainstream biomedical research. In this thesis, a microfluidic platform is presented that allows the encapsulation of viable cells in agarose microcapsules for applications in cell–based therapy. As an improvement to pre-existing methods of cell encapsulation, the proposed system combines continuous high throughput cell-encapsulation with on-chip microcapsule gelation and purification.
Keywords: Microfluidics; Microcapsules; Cell encapsulation; Agarose; Cell therapy; Regenerative medicine; Lab-on-a-chip